ПЕРЕНАПРУГИ ПІД ЧАС ДУГОВИХ ОДНОФАЗНИХ ЗАМИКАНЬ НА ЗЕМЛЮ В ЕЛЕКТРИЧНИХ МЕРЕЖАХ 35 КВ - Сегеда, М.С.; Равлик, О.М.; Бахор, З.М.; Яцейко, А.Я. (Інститут електродинаміки Національної академії наук України, 2021)
The results of the study of overvoltages during arc single-phase earth faults of intermittent nature in the 35 kV electric network with isolated neutral are presented. Computer simulations of transients in the electrical network have obtained the maximum multiplicities of overvoltages at the point of occurrence of single-phase arc earth faults, which exceed theoretically expected according to known theories of the occurrence and development of overvoltages. The change of the overvoltage level on the 35 kV busbars of the network substations, electrically connected to the place of occurrence of the single-phase earth fault, and the influence of the cable line on the overvoltage multiplicity are shown.  Ref. 12, fig. 3, table.